Sinonasal Leiomyosarcoma: Clinicopathological Analysis of Nine Cases with Emphasis on Common Association with Other Malignancies and Late Distant Metastasis - Agaimy, Abbas; Semrau, Sabine; Koch, Michael; Thompson, Lester D.R. (Head and Neck Pathology, 2018)
Sinonasal tract (SNT) leiomyosarcoma (LMS) is exceedingly rare with < 100 cases reported. Their relationship to retinoblastoma and other malignancies, along with previous irradiation has not been clarified. Routine and consultation cases were reviewed for histologically and immunohistochemically proven SNT LMS. The tumors were tested with antibodies against α-smooth muscle actin, desmin, h-caldesmon, HMB45, S100 protein, Rb1, MDM2, CDK4 and EBV (EBER-ISH). Nine tumors affecting 5 males and 4 females aged 26 to 77 years (median: 48 years) were identified in the maxillary sinus (n = 4), nasal cavity (n = 3) and combined SNT (n = 2). Three patients had previous irradiation (2 for retinoblastoma, 1 for fibrous dysplasia) and 1 patient had chemotherapy and stem cell transplantation for Hodgkin lymphoma. One patient had prostatic adenocarcinoma (prior) and rectal adenocarcinoma (post) to the LMS. All patients with follow-up developed either local recurrences and/or metastases, principally to lung (time to metastasis: 16-156 months, mean 62 months). Histologically, 6 tumors were conventional high-grade LMS, two had glycogen-rich clear cell (PEComa-like) morphology and one was spindle cell low-grade. The latter showed grade 2 in the recurrence and grade 3 in the lung metastases. Two cases showed dedifferentiation to anaplastic pleomorphic (inflammatory MFH-like) phenotype. Immunohistochemistry revealed diffuse expression of at least 2 smooth muscle markers in 8 and only actin in one case/s. All other markers were negative. RB1 loss was observed in 6/8 cases tested. Sinonasal tract leiomyosarcomas are rare aggressive sarcomas that frequently develop in a background of previous cancer therapy (4/9), most frequently irradiation. Their varied morphology underlines the wide differential diagnostic considerations. Long-term survival may be achieved with aggressive multimodal therapy.
EVALuna2:34895